Malnutrition-related parasite dissemination from the skin in visceral leishmaniasis is driven by PGE2-mediated amplification of CCR7-related trafficking of infected inflammatory monocytes. - E Yaneth Osorio; Ashanti Uscanga-Palomeque; Grace T Patterson; Erika Cordova; Bruno L Travi; Lynn Soong; Peter C Melby (PLoS Neglected Tropical Diseases, 2023)
People are infected with Leishmania donovani when the parasite is deposited in the dermis during the blood meal of the sand fly vector. Most infected people develop a subclinical latent infection, but some develop progressive visceral leishmaniasis. Malnutrition is a risk factor for the development of active VL. We previously demonstrated increased parasite dissemination from the skin to visceral organs in a murine model of malnutrition. Here we investigated the mechanism of early parasite dissemination. After delivery of L. donovani to the skin, we found enhanced capture of parasites by inflammatory monocytes and neutrophils in the skin of malnourished mice. However, parasite dissemination in malnourished mice was driven primarily by infected inflammatory monocytes, which showed increased CCR7 expression, greater intrinsic migratory capacity, and increased trafficking from skin to spleen. PGE2 production, which was increased at the site of skin infection, increased monocyte CCR7 expression and promoted CCR7-related monocyte-mediated early parasite dissemination in malnourished mice. Parasite dissemination in monocytes was reduced by inhibition of PGE2, knockdown or silencing of CCR7 in monocytes, and depletion of inflammatory monocytes through administration of diphtheria toxin to CSFR1-DTR transgenic mice that have monocyte-specific DT receptor expression. CCR7-driven trafficking of infected inflammatory monocytes through the lymph node was accompanied by increased expression of its ligands CCL19 and CCL21. These results show that the CCR7/PGE2 axis is responsible for the increased trafficking of L. donovani-infected inflammatory monocytes from the skin to the spleen in the malnourished host. Undernutrition and production of PGE2 are potential targets to reduce the risk of people developing VL. Nutritional interventions that target improved immune function and reduced PGE2 synthesis should be studied in people at risk of developing VL.